Thymoquinone affects the gemcitabine sensitivity of pancreatic cancer by regulating collagen via hypoxia inducible factor-1α - Zhao, Zhanxue; Liu, Linxun; Chen, Hekai; Li, Shuai; Guo, Yan; Hou, Xiaofan; Yang, Jinyu (Frontiers in Pharmacology, 2023)
Objective: To clarify the potential therapeutic effects of thymoquinone (TQ) on pancreatic cancer and its gemcitabine (GEM) sensitivity. Methods: The expression levels of hypoxia inducible factor-1α (HIF-1α), collagens, and transforming growth factor-β1 (TGFβ1) in pancreatic cancer and para-carcinoma tissues were compared using immunohistochemical methods, and their relationships with TNM staging were analyzed. The TQ effects on apoptosis, migration, invasion, and GEM sensitivity of pancreatic cancer cells were assessed using in vitro and in vivo experiments. Western blot and immunohistochemistry were used to detect the expression levels of HIF-1α, extracellular matrix (ECM) production pathway-related proteins, and TGFβ/Smad signaling pathway-related proteins. Results: The expression levels of HIF-1α, COL1A1, COL3A1, COL5A1, and TGFβ1 in pancreatic cancer tissues were significantly higher than those in para-carcinoma tissues and correlated with TNM staging. TQ and GEM administration inhibited the migration and invasion of the human pancreatic cancer cell line PANC-1 and promoted the apoptosis of PANC-1 cells. The combination of TQ and GEM was more effective than GEM alone. Western blot analysis showed that the expression levels of HIF-1α, ECM production pathway-related proteins, and TGFβ/Smad signaling pathway-related proteins were significantly decreased when TQ was used to treat PANC-1 cells, and the expression levels of these proteins in the TQ+GEM group were significantly more decreased than those in the GEM group. Overexpression or knockdown of HIF-1α in PANC-1 cells showed the same effects as those induced by TQ administration. In vivo experiments showed that in PANC-1 tumor-bearing mice, tumor volume and tumor weight in mice treated with GEM and TQ were significantly lower than those in control or GEM-treated mice, whereas cell apoptosis was significantly increased. Western blot and immunohistochemistry results showed that the levels of HIF-1α, ECM production pathway-related proteins, and TGFβ/Smad signaling pathway-related proteins in the GEM+TQ treatment group were further decreased compared to the control group or the GEM treatment group. Conclusion: In pancreatic cancer cells, TQ can promote apoptosis, inhibit migration, invasion, and metastasis, and enhance the sensitivity to GEM. The underlying mechanism may involve the regulation of ECM production through the TGFβ/Smad pathway, in which HIF-1α plays a key role.